POST-HEALTH EVALUATION BUILDING LINES AND ADMINISTRATION DEPARTMENT OF EDUCATION TECHNIQUE BUILDING FACULTY OF ENGINEERING UNY - Sugestiyadi, Bambang (Jurnal Penelitian Saintek, 2015)
The study of the post occupancy evaluation of the lecturing and administration buildings of the Department of the Construction Engineering Teacher Training of the Faculty of Technique of Yogyakarta State University is limited at the indicative level of the lecturing and administration buildings. It aims at investigating the technical and functional aspects of the lecturing and administration rooms of the Department of the Construction Engineering Teacher Training of the Faculty of Technique ofYogyakarta State University. It is conducted in 5 months of the lecturing period 199912000, with the analysis unit of the Department of the Construction Engineering with all of its activity aspects. The observing focuses of the study are a) the technical aspect, including: 1) lighting, 2) ventilation, 3) security, 4)fire fighting, 5) maintenance; b) the functional aspect, including: 1) room organization, 2) room capacity, 3) circulation, 4) communication, 5) the possibility to change. The data is collected using interview, field observation and documentation. The content validity is tested on relational judgmental basis. The results of the study show that in almost 50% of the lecturing period of the odd semester of 1999/2000 the lecturing room capacity is "less ", It is also found that the ideal and comfortable lecturing rooms are those with the capacity of 30-35 individuals per classroom. Based on the results of the study, it is necessary to consider the addition of the lecturing rooms with the "big" capacity of 100 individuals. And, based on the results of the evaluation of the capacity of the administration and lecturer rooms show that 90% of the capacity of the rooms do not meet the working room standard. The condition of the comfort and the security of the rooms do not meet the requirements. Based on the results of the study it is necessary to develop the administration and the lecturer rooms into a "vertical" direction that they meet the comfortable working room standard.